Collaboration and knowledge creation processes through co-authored scientific articles between Africa, Sweden and Finland - Jauhiainen Jussi S. (Nordic Africa Research Network, 2025)
The European Union and many individual European countries emphasize the value of partnerships with Africa, including in research and development. This article examined research collaborations and related knowledge creation processes between Africa, Sweden, and Finland. To analyse this topic, the article develops a nuanced model of centres and peripheries in knowledge production. The focus was on scientific outputs, particularly coauthored scientific articles in peer-reviewed international journals, with at least one affiliation from Africa and another from Sweden or Finland. The quantity of articles their topics, research areas, and scientific impacts were analysed, as well as the authors’ affiliations and backgrounds. Between 2015 and 2021, almost 10,500 international peer-reviewed scientific coauthored articles were indexed in the Web of Science database coauthored by scholars affiliated with Africa and Sweden, and almost 4,600 such articles by scholars affiliated with Africa and Finland. On average, less than one collaboration article per year appeared with coauthors from Sweden or Finland and from most African countries. Proportionally more articles were published by scholars affiliated with those African countries in which Sweden and Finland conducted development policy initiatives. South African universities were present in almost half of the coauthored articles with Sweden and Finland. The Karolinska Institute and the University of Lund in Sweden, and the University of Helsinki in Finland, were the most active research collaborators with Africa. Only about one-fifth of coauthored articles focused specifically on Africa. Overall, collaborations between scholars in the academic centres of the Global North and those in the academically more peripheral African universities are hierarchical. Most coauthored international peer-reviewed scientific articles from Africa connected to global academic networks with Anglo-American universities leading in medical science and science. More engaged reciprocal collaborations are needed between Africa, Sweden, and Finland. Such critical edges of knowledge creation would promote novel and emancipating scientific perspectives and practices.